On social evolution : phenomenon and paradigm - Tang, Shiping, 1967- (New York : Routledge, 2020)
"Tang provides a coherent and systematic exploration (statement/exposition better?) of social evolution as a phenomenon and as a paradigm. He critically builds on existing discussions on social evolution, while drawing from a wide range of disciplines, including archaeology, evolutionary anthropology, sociology, economics, political science, the philosophy of social sciences, and evolutionary biology. Clarifying the relationship between biological evolution and social evolution, Tang lays bare the ontological and epistemological principles of the Social Evolutionary Paradigm. He also presents operational principles and tools for deploying this paradigm to understand empirical puzzles about human society. This is a vital resource for students, practitioners and philosophers of all social sciences"--
OCLC-licensed vendor bibliographic record.
Keywords: Social evolution; SOCIAL SCIENCE / Sociology / General; PHILOSOPHY / General